Intellectual capital: Evidence from banking industry - Somayeh Boostani; Shabnam Fotovvat; Karam Safari (Management Science Letters)
This paper investigates different components on intellectual capital including human capital, structural capital and customer capital in banking industry in city of Salmas, Iran. The study uses the questionnaire developed by Bontis (1998) [Bontis, N. (1998). Intellectual capital: an exploratory study that develops measures and models. Management Decision, 36(2), 63-76.] to measure the effects of human capital. The questionnaire consists of 42 questions and all of them are designed in Likert scale. Cronbach alphas for human capital, structural capital and relationship capital were calculated as 0.79, 0.76 and 0.72, respectively. The implementation of Kolmogorov-Smirnov test has indicated that the data were normally distributed. Using t-student test, the study determined that while management team did not pay enough attention on human capital, there were some statistically significant evidence that social and relationship capitals gained good attention.